Dynamic Assembly of Human Salivary Stem/Progenitor Microstructures Requires Coordinated α1β1 Integrin-Mediated Motility - Wu, Danielle; Witt, Robert L.; Harrington, Daniel A.; Farach-Carson, Mary C. (Frontiers in Cell and Developmental Biology, 2019)
A tissue engineering approach can provide replacement salivary gland structures to patients with hyposalivation disorders and xerostomia. Salivary human stem/progenitor cells (hS/PCs) were isolated from healthy regions of parotid glands of head and neck surgery patients, expanded, then encapsulated in biocompatible hyaluronate (HA)-based hydrogels. These bioactive hydrogels mimic a mesenchyme suitable for the dynamic assembly, growth and reorganization of salivary gland components. This study examined the dynamics of salivary microstructure formation, growth and reorganization using time-lapse imaging over 15 hours. Immunofluorescence detection monitored production of individual basement membrane components forming around developing microstructures, and Ki67 assessed proliferation. Dynamic movements in hydrogels were quantified by measuring angular velocity (ω) of rotating salivary microstructures and changes in basement membrane architecture during microstructure growth. Integrin involvement in the dynamic reassembly was assessed using knockdown and inhibitor approaches. Single hS/PCs assembled into spherical microstructures typically containing 3-8 cells. In larger macrostructures, proliferation occurred near the peripheral basement membrane that underwent growth-associated cycles of thinning and collapse. De novo secretion of laminin/collagen IV from reorganizing hS/PCs preceded that of perlecan/HSPG2. Microstructures routinely expressed β1 integrin-containing complexes at basement membrane-associated regions and exhibited spontaneous and coordinated rotation during basement membrane maturation. β1 integrin siRNA knockdown at the single-cell state prevented hS/PC microstructure growth. After microstructure formation, β1 integrin knockdown reduced rotation and mean ω by 84%. Blockade of the α1 integrin subunit (CD49α) that associates with β1 reduced mean ω by 66%. Studies presented here show that initial hS/PC structure growth and basement membrane maturation depends on α1β1-integrin mediated signaling. Coordinated cellular motility during neotissue reorganization reminiscent of salivary gland acini was critically dependent both on hS/PC-secretion of laminin, collagen type-IV, and perlecan/HSPG2 and the force-driven interactions of α1β1-integrin activation. We conclude that α1β1-integrin plays a critical role in establishing human salivary gland coordinated structure and function, and that its activation in tissue engineered systems is essential to tissue assembly.